Molecular Alterations in Pediatric Low-Grade Gliomas That Led to Death. Issue 11 (27th September 2021) - Ahrendsen, Jared T; Sinai, Claire; Meredith, David M; Malinowski, Seth W; Cooney, Tabitha M; Bandopadhayay, Pratiti; Ligon, Keith L; Alexandrescu, Sanda
Abstract: Pediatric low-grade gliomas (PLGGs) have excellent long-term survival, but death can occasionally occur. We reviewed all PLGG-related deaths between 1975 and 2019 at our institution: 48 patients were identified; clinical data and histology were reviewed; targeted exome sequencing was performed on available material. The median age at diagnosis was 5.2 years (0.4–23.4 years), at death was 13.0 years (1.9–43.2 years), and the overall survival was 7.2 years (0.0–33.3 years). Tumors were located throughout CNS, but predominantly in the diencephalon. Diagnoses included low-grade glioma, not otherwise specified (n = 25), pilocytic astrocytoma (n = 15), diffuse astrocytoma (n = 3), ganglioglioma (n = 3), and pilomyxoid astrocytoma (n = 2). Recurrence occurred in 42/48 cases, whereas progression occurred in 10. The cause of death was direct tumor involvement in 31/48 cases. Recurrent drivers included KIAA1549-BRAF (n = 13), BRAF(V600E) (n = 3), NF1 mutation (n = 3), EGFR mutation (n = 3), and FGFR1-TACC1 fusion (n = 2). Single cases were identified with IDH1(R132H), FGFR1(K656E), FGFR1 ITD, FGFR3 gain, PDGFRA amplification, and mismatch repair alteration. CDKN2A/B, CDKN2C, and PTEN loss was recurrent. Patients who received only chemotherapy had worse survival compared with patients who received radiation and chemotherapy. This study demonstrates that PLGG that led to death have diverse molecular characteristics. Location and co-occurring molecular alterations with malignant potential can predict poor outcomes.